Mapping physical activity research in reputable international journals: a bibliometric analysis - Karisdha Pradityana; Widiastuti Widiastuti; Samsudin Samsudin; Yasep Setiakarnawijaya; Khaeroni Khaeroni (Universitas Negeri Malang, 2023)
Background: An in-depth understanding of how physical education can catalyze physical activity among students and society at large is becoming increasingly important. Objective: This study aims to determine the development of scientific publications, mapping the scope and theme of publications related to physical activity published in Scopus-indexed journals from 2018 to 2022. The research questions in this study are: (1) How is the development of publications related to physical activity? (2) What are the most cited articles by title? (3) What themes are related to physical activity? (4) What themes are the most interesting to research in the future? Methods: The publish or perish tool is used to access the Scopus database, which is used in this study. Using the keyword